Pharmacological changes in the smallest units of the body - Fanil Faridovich Zagrutdinov; Baltaboyeva Dilbar Farzurahmanovna; Mamadaliyev Sherzod Iminjon o’g’li; Egamberdiyev Jasurbek Jumanazar o’g’li; Sobirov Olimjon Odiljon o’g’li (Genius Journals, 2022)
In this paper, quantitative changes in lipid content in the liver mitochondria were measured at different times after heliogram was administered to rats to determine the pathogenetic significance of hepatitis in the liver.
Keywords: Mitochondria; lipid; liver; hepatitis